2010
DOI: 10.1007/978-3-642-15214-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Binarisation Techniques for the Processing of Ancient Manuscripts

Abstract: International audienceAncient manuscripts have been preserved by many organizations so as to protect these documents and retrieve traditional knowledge. With the advanced computer technology, digitized media is now commonly used to record these documents. One objective of such work is to develop an efficient image processing system that could be used to retrieve knowledge and information automatically from these ancient manuscripts. Binarization is a preprocessing technique used to extract text and characters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The performance of binarization techniques has a great impact and directly affects the performance of the recognition task [35]. Non-optimal binarization methods produce unrecognizable characters with noise [16]. Many binarization methods have been reported.…”
Section: Binarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of binarization techniques has a great impact and directly affects the performance of the recognition task [35]. Non-optimal binarization methods produce unrecognizable characters with noise [16]. Many binarization methods have been reported.…”
Section: Binarizationmentioning
confidence: 99%
“…These methods have been tested and evaluated on different types of document collections. Based on the choice of the thresholding value, binarization methods can generally be divided into two types, global binarization and local adaptive binarization [16]. Some surveys and comparative studies of the performance of several binarization methods have been reported [35,36].…”
Section: Binarizationmentioning
confidence: 99%
“…For example, the IHCR challenges for historical documents discovered in the palm leaf manuscripts, written using the script originating from the region of Southeast Asia, such as Indonesia, Cambodia, and Thailand. Ancient palm leaf manuscripts from Southeast Asia have received great attention from historian and also researchers in the field of document image analysis, for example some works on document analysis of palm leaf manuscript from Thailand [1,2] and from Indonesia [3,4]. The physical condition of the palm leaf documents is usually degraded.…”
Section: Introductionmentioning
confidence: 99%
“…In the last five years, ancient palm leaf manuscripts have received great attention from researchers in the field of document image analysis. For example, a digitization project for palm leaf manuscripts from Cambodia 1 and Thailand [1], [2].…”
Section: Introductionmentioning
confidence: 99%